2013
DOI: 10.1016/j.joca.2012.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Medial arch supports do not significantly alter the knee adduction moment in people with knee osteoarthritis

Abstract: This study showed no mean change in any of the measured indices of medial knee load with medial arch supports. No immediate changes in knee pain were evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(40 reference statements)
1
17
1
Order By: Relevance
“…However, Hinman et al 17 found no statistically significant changes with medial arch supports in any aspect of the KAM or external hip adduction moment, while Turpin et al 18 found no changes with shock absorbing insoles in any aspect of the KAM.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, Hinman et al 17 found no statistically significant changes with medial arch supports in any aspect of the KAM or external hip adduction moment, while Turpin et al 18 found no changes with shock absorbing insoles in any aspect of the KAM.…”
Section: Resultsmentioning
confidence: 98%
“…Only one study each was identified that examined the use of medial arch supports17 or shock absorbing insoles,18 and therefore data pooling was not possible. However, Hinman et al 17 found no statistically significant changes with medial arch supports in any aspect of the KAM or external hip adduction moment, while Turpin et al 18 found no changes with shock absorbing insoles in any aspect of the KAM.…”
Section: Resultsmentioning
confidence: 99%
“…The hypothesis above needs to be further studied, emphasizing the importance of coordination between the lateral wedge and medial arch. It is worth mentioning that we have not analyzed the participants’ different responses and individual variations, which could be conspicuous as Hinman et al [38] observed. In addition, there are only 2 comparisons included in the neutral insole group for the second EKAM.…”
Section: Discussionmentioning
confidence: 98%
“…[47,59] The reported effects of the neutral insole are not consistent in recent studies. [38,65] Although meta-analysis pooling of all studies showed statistically significant associations between the use of LWAS and reductions of the first peak EKAM, second peak EKAM and KAAI during walking for people with medial knee OA, different results were observed when comparing with various control conditions. With regard to the first peak EKAM, the use of LWAS results in a small but statistically significant reduction when the control group is the neutral insole, whereas no significant difference existed in the shoe-only or flat insole condition.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the addition of medial arch supports into shoes has been associated with increased knee loads [25,26], suggesting that increasing foot supination and/or restricting foot pronation may have adverse effects on loading at the knee joint. In this context, it is of interest to note that the third, fourth and sixth styles most commonly advised to be bad for knee OA symptoms by health professionals were flexible thin soled shoes, barefoot and flat shoes, respectively.…”
Section: Discussionmentioning
confidence: 99%